High porosity cellulose nanopapers as reinforcement in multi-layer epoxy laminates - Mautner, Andreas; Wan Nawawi, Wan Mohd Fazli; Koon-Yang, Lee; Bismarck, Alexander (Elsevier Ltd, 2020)
Utilizing high-performance cellulose nanopapers as 2D-reinforcement for polymers allows for realizing high-loading-fraction (80 vol-%), high-performance (strength > 150 MPa, modulus > 10 GPa) laminated nanopaper reinforced epoxy composites. Such cellulose nanopapers are inherently dense, which renders them difficult to be impregnated with the epoxy-resin. High-porosity nanopapers facilitate better resin impregnation, truly utilizing the properties of single cellulose nanofibres instead of the nanofibre network. We report the use of high-porosity (74%) but low strength and modulus bacterial cellulose (BC) nanopapers, prepared from BC-in-ethanol dispersion, as reinforcement for epoxy-resin. High-porosity nanopapers allowed for full impregnation of the BC-nanopapers with epoxy-resin. The resulting BC-reinforced epoxy-laminates possessed high tensile modulus (9 GPa) and strength (100 MPa) at a BC loading of 30 vol-%, resulting from very low void-fraction (3 vol-%) of these papregs compared to conventional nanopaper-laminates (10+ vol.-%). Better resin impregnation of less dense nanocellulose networks allowed for maximum utilization of stiffness/strength of cellulose nanofibrils. © 2020 Elsevier Ltd